2022
DOI: 10.1002/advs.202201352
|View full text |Cite|
|
Sign up to set email alerts
|

Stable Transgenic Mouse Strain with Enhanced Photoactivatable Cre Recombinase for Spatiotemporal Genome Manipulation

Abstract: Optogenetic genome engineering is a powerful technology for high-resolution spatiotemporal genetic manipulation, especially for in vivo studies. It is difficult to generate stable transgenic animals carrying a tightly regulated optogenetic system, as its long-term expression induces high background activity. Here, the generation of an enhanced photoactivatable Cre recombinase (ePA-Cre) transgenic mouse strain with stringent light responsiveness and high recombination efficiency is reported. Through serial opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…11 ). Indeed, previous research demonstrated that blue light from an LED array can effectively reach mouse liver tissues 31 . Compared to mice injected with the padCas13-2 editor but not exposed to the light stimulation, the RNA editing-enabled mice exhibited a substantially greater luciferase signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 ). Indeed, previous research demonstrated that blue light from an LED array can effectively reach mouse liver tissues 31 . Compared to mice injected with the padCas13-2 editor but not exposed to the light stimulation, the RNA editing-enabled mice exhibited a substantially greater luciferase signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, various advancements of the original recombination system have emerged to achieve even finer spatiotemporal comprehension (Shcholok and Eftekharpour, 2023 ). These include the tamoxifen-inducible Cre-ER T2 system (Belteki et al, 2005 ; Heldt and Ressler, 2011 ; Hui et al, 2022 ; Kellogg et al, 2023 ), photoactivatable Cre recombinases (Yoshimi et al, 2021 ; Li et al, 2022 ), Cre/Dre dual recombinase systems (Kouvaros et al, 2023 ) and split Cre systems (Khoo et al, 2020 ; Kim et al, 2021 ), among others. Some of these configurations are of extreme help to easily explore the time and the space, inducing the pathological insult within cell types at various embryonic and postnatal timepoints with high specificity.…”
Section: Exploring Space and Time: Novel Insights From Animal Modelsmentioning
confidence: 99%
“…Optogenetic engineering has been developed to some extent. It has been used for detailed in vivo single-cell analysis because of its efficiency and spatiotemporal specificity ( Yao et al, 2020 ; Li et al, 2022a ; Geiller et al, 2022 ). Here, we describe the advances in cell lineage tracing technology, with a focus on Cre/LoxP recombinase systems ( Figure 1 ).…”
Section: Tracking the Targets All The Way: Lineage Tracingmentioning
confidence: 99%